STATE OF KNOWLEDGE AND RESEARCH PROBLEMS OF SUITES’ STRATOTYPES AND REFERENCE SECTIONS OF THE LOWER CRETACEOUS STRATA IN THE MOUNTAINOUS CRIMEA - Anfimova, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Stratotypes and key sections taken as standards of the local stratigraphic units – suites and strata – have a great scientific and practical value, play an important didactic role, can act as objects of geological tourism. A standard section is a starting point for scientific research on additional exploration of a stratigraphic unit, the refinement of the age of its constituent sediments, etc. The purpose of this work is to assess the state of knowledge of the Mountainous Crimea Lower Cretaceous suites’ stratotypes and strata’ key sections, to identify the problems of their research. The state of knowledge of suites’ stratotypes and strata’ key sections has been analyzed based on published literature and production reports data. The history of the stratigraphic division of the Mountainous Crimea Lower Cretaceous deposits has been traced. The summary stratigraphic section of the Mountainous Crimea Lower Cretaceous deposits, and the stratotypes and key sections layout are presented. Numerous examples illustrate some disagreement between different researchers on the stratigraphic division of the Mountainous Crimea Lower Cretaceous deposits. The problems in research of standard sections are revealed. These differences and research problems can be summarized as follows: (1) There are differences in understanding of stratigraphic units’ volume and content. (2) Units are dated variously by different authors. (3) Researchers use different names to notate the same units. (4) The same names are used to notate units different by their content. (5) Different researchers give unequal rank to the same units. (6) For a number of stratigraphic units the reference sections are not highlighted. (7) Lack of knowledge, lack of data on the exact location for some standard sections. (8) Some type sections have been described in outcrops of artificial origin that, in some cases, hinders their accessibility. It can be concluded that the reference sections allocated in the Mountainous Crimea Lower Cretaceous deposits, have different degrees of scrutiny, but overall degree of their scrutiny can be characterized as weak. The study has demonstrated the necessity of further work on exploration of the type sections of the Mountainous Crimea Lower Cretaceous local stratigraphic units. Sustainable interest of researchers to the problems of the Lower Cretaceous deposits stratigraphy, contradictory data on the age, volume and content of stratigraphic units are the justification for standard sections preservation.